2015
DOI: 10.1002/bdd.1945
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of loxoprofen to a pharmacologically active metabolite and its disposition kinetics in human skin

Abstract: Loxoprofen (LX) is a prodrug-type non-steroidal anti-inflammatory drug which is used not only as an oral drug but also as a transdermal formulation. As a pharmacologically active metabolite, the trans-alcohol form of LX (trans-OH form) is generated after oral administration to humans. The objectives of this study were to evaluate the generation of the trans-OH form in human in vitro skin and to identify the predominant enzyme for its generation. In the permeation and metabolism study using human in vitro skin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…An ideal topical application represents a much greater accumulation of the drugs in the skin compared with that in the systemic circulation and is a more efficient method for targeting to bypass systemic toxicity (46). Our skin absorption data showed that both HFP031 and HFP034 were absent in the Franz cell receptor, implying a targeting capability to the skin with minimal systemic absorption.…”
Section: Discussionmentioning
confidence: 78%
“…An ideal topical application represents a much greater accumulation of the drugs in the skin compared with that in the systemic circulation and is a more efficient method for targeting to bypass systemic toxicity (46). Our skin absorption data showed that both HFP031 and HFP034 were absent in the Franz cell receptor, implying a targeting capability to the skin with minimal systemic absorption.…”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, whether the cutaneous absorption of flavonoids is sufficient to trigger the bioactivity is questionable. An ideal topical administration has a much higher absorption accomplished in the cutaneous reservoir compared to that in the systemic circulation to achieve efficient targeting and escape systemic toxicity [ 14 ]. We examined the skin delivery and anti-inflammatory activity of aglycone and glycoside flavonoids to select the potential candidates for topical application with the aim of prevention or therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The major metabolic pathway involved in the biotransformation of loxoprofen, a prodrugtype non-steroidal anti-inflammatory drug used orally and topically, is carbonyl reduction to a pharmacologically active alcohol metabolite (Ohara et al, 1995). The predominant enzyme which catalyzes this reaction in human liver as well as in skin was identified to be CBR1 (Ohara et al, 1995;Sawamura et al, 2015). In contrast, the structurally similar drug ketoprofen is metabolized exclusively by AKRs (Ohara et al, 1995).…”
Section: The Cytostatics Doxorubicin and Daunorubicinmentioning
confidence: 99%